Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1086/229330
|View full text |Cite
|
Sign up to set email alerts
|

The Divergence of Black and White Marriage Patterns

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(109 citation statements)
references
References 33 publications
5
100
3
Order By: Relevance
“…ff4 (Bennett, 1989), evidence was found that with increases in women's wages, the probability of being currently married increases, although fertility may be expected to continue to decline among both black and white women as their labor market opportunities improve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ff4 (Bennett, 1989), evidence was found that with increases in women's wages, the probability of being currently married increases, although fertility may be expected to continue to decline among both black and white women as their labor market opportunities improve.…”
Section: Discussionmentioning
confidence: 99%
“…The median age at marriage has been increasing, and a growing proportion of women are not marrying, particularly among blacks (Bennett et al, 1989). The fraction of births out of wedlock had increased to 56 percent for blacks by 1979 and to 18 percent for whites (U.S. Bureau of the Census, 1982Census, , 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for white cohorts, there is some indication of support for our hypothesis that education in young adulthood represents an investment in human capital that results in delaying childbearing and possibly marriage, as well. It may also be related to whites' greater probability of marriage over the life span and after giving birth without being married (Bennett, et al, 1989;Harknett and McLanahan 2004). For black cohorts, the dynamics appear different, with greater investment in education perhaps resulting in a greater probability to be financially independent and thus making childbearing outside of marriage more economically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…A second possible influence, however, is the "independence effect," where women with more education (and, hence, likely greater potential earnings) are less reliant on a marriage partner in order to bear and raise children (Becker 1981;Bennett et al 1989;Espenshade 1985: 222-225). Thus, a cohort's higher enrollment in education during the late teens and early adult years could be positively, negatively or not associated with NFRs throughout a cohort's primary childbearing years, contingent on the relative magnitudes of the "discouragement/delay effect" versus the "independence effect."…”
Section: Cohort Opportunity Structuresmentioning
confidence: 99%
“…It seems critical to reflect on social, psychological, and cultural factors at the micro-level that play a role in Black marriages (Bennett, Bloom, & Craig, 1989;Cherlin, 1992;Tucker & Mitchell-Kernan, 1995). With regard to social and psychological factors, similarities in couples' interpersonal resources contribute to compatibility in marriage (Gibson-Davis, Edin, & McLanahan, 2005;Marks, Hopkins, Chaney, Monroe, Nesteruk, & Sasser, 2008;Smock, Manning, & Porter, 2005).…”
Section: Introductionmentioning
confidence: 99%